Effects of Functionalized Polyethylene and Styrene ButadIene Styrene Polymers on Performance Grade of Local Asphalt (Journal of Engineering, 2012)
Rutting is one of the major distresses in pavement. The objective of this paper is to develop an improved asphalt binder grading system for Iraq based on the principal of Superpave system, and increasing performance grade of product asphalt binder in Iraq using polymers without raising the viscosity of the binder. Two types of polymers are used, Plastomers, Functionalized Polyethylene (PE) which is developed by asphalt research group in Wisconsin University in the USA, and Elastomers, Styrene Butadiene Styrene (SBS) with and without cross linker. Mastercurve are drown for these modified binders, Rolling thin film aged, to show effects on rheological properties at high temperature for complex modulus (G*) and phase angle (δ). It concluded that 3.5% of Functionalized Polyethylene polymer (PE) is more effective than 4% of Styrene Butadiene Styrene (SBS) to shift up performance grade of local asphalt binder two grades to be PG (76-16). Furthermore, the viscosity of binders increasing about 200% when using 4 % SBS, while no significant effect on viscosity when using 3.5 % of PE, therefore, there is no need to increase temperature of mixing and compaction which may be effect on polymers In addition G*/sinδ is increased by a ratios of 1.6 to 2.96 for 2%, 4% respectively of SBS-based modifier (RTFO aged) and 1.4 to 3 for 2%, 3.5% respectively of PE-based polymers modifier. It can be seen that PE reduce G*.sinδ about 10%, while SBS increase G*.sinδ about 30% and PE reduces the stiffness of asphalt binder about 15 % at low temperature which make PE more effective, there is no significant effects on m-value.